Efficiency Of STMIK Hang Tuah Pekanbaru Stationery Inventory Office Using Monte Carlo Method - Rian Ordila (Journal of Applied Engineering and Technological Science (JAETS), 2020)
Inventory management in Office Stationery needs (ATK) is instrumental in supporting administrative activities. Not terinvetaris well, resulting in the use of goods is not optimal and increase spending on this ATK. For that required a system that can manage this ATK supplies. so that in the prediction of ATK inventory can coordinate and minimize expenditure of STMIK Hang Tuah Pekanbaru expenditure. The data obtained in this research is ATK At High School of Information and Computer Management (STMIK) Hang Tuah Pekanbaru sourced from Head of Equipment Section such as paper type A4 and F4, Paperclip, Map and Printer Ink. ATK is always experiencing shortage or also excess needs. With the Monte Carlo Method, STMIK Hang Tuah Pekanbaru will be able to determine the Pattern of ATK Supplies requirement in STMIK Hang Tuah Pekanbaru and the method can give a decision in determining the pattern of ATK request that will be requested to the employee. The result of the experiment of this method is to obtain the average number of procurement requests and the average number of procurement. Estimates of the Monte Carlo simulation strategic plan that has been done will yield an estimated information on the average amount of procurement as 16 packs and the estimated average monthly expenditure of Rp 21,333.- With the amount of calculations obtained then the Office Stationery to be purchased can be estimated and inventory can be provided to meet the demand for campus needs in 2018